2004
DOI: 10.1177/039139880402701110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Direct Toxicity of Trioctyltrimellitate (TOTM), di(2-ethylhexyl) Phthalate (DEHP) and their Hydrolysis Products on Isolated Rat Hepatocytes

Abstract: Plasticizers are added to polyvinyl chloride (PVC) to confer flexibility to the polymer. Di-(2-ethylhexyl) phthalate (DEHP) is the most commonly used of them. However, due to its non covalent bond to the PVC, DEHP tends to vaporize easily. A significant exposure has been recorded in dialyzed patients since medical tubings. Most animal species metabolize DEHP rapidly into mono-ethylhexyl phthalate (MEHP) and 2-ethylhexanol (2-EH). Because of the suspected toxicity of DEHP, an alternative plasticizer, trioctyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…117 After intraperitoneal injection, 2EH did not induce a significant production of hydrogen peroxide generated by peroxisome proliferators in the rat hepatocytes. 118…”
Section: Intraperitoneal Exposurementioning
confidence: 99%
“…117 After intraperitoneal injection, 2EH did not induce a significant production of hydrogen peroxide generated by peroxisome proliferators in the rat hepatocytes. 118…”
Section: Intraperitoneal Exposurementioning
confidence: 99%
“…Tasci et al [21] stated that disorganization of nuclear content as margination and clumping of chromatin in saline treated animals may be morphological evidence of injury in the nucleus. Kambia et al [11] reported that, following TOTM administration, high rate of new mitochondrial membrane formation is due to increased endogenous mitochondrial protein synthesis in addition to increased rate of membrane phospholipid synthesis by about 20%.Sections of the same group showed dilated tubules of sER of hepatocytes. Since sER plays a prominent role in the metabolic transformation of drugs and toxins.…”
Section: Discussionmentioning
confidence: 96%
“…TOTM have been found to be non-mutagenic. It is not able to bind to peroxisome proliferator-activated receptors (PPARs) [11].…”
Section: Introductionmentioning
confidence: 99%
“…First results indicate that TOTM actually possesses a lower toxicity than DEHP [2,[18][19][20]. Moreover, a higher chemical stability can be assumed indicated by a significantly decreased leachability of TOTM from PVC medical devices into intravenous preparations [21] and into blood [10].…”
Section: Introductionmentioning
confidence: 95%